The race talk - Orelus, Pierre W. (Emerald Publishing Limited : Information Age Pub., 2012)
Drawing on critical race theory, this book critically examines race through a mosaic lens pointing out various issues directly connected to it, such as racial identity politics, racism, multiracialism, interracial relationships, and the hegemony of whiteness. This book goes further to analyze the manner in which socially constructed racial stereotypes contribute to and are used to justify the poor socio-economic situation and marginalization of People of Color, particularly the poor ones. Designed for a broad range of readers, this book aims to open up democratic spaces for genuine discussions about racial issues.